Pd-Pt nanoparticles for plasmonic sensing of hydrogen in humid environments - Colliander, William (My University)
Using hydrogen as energy storage and as fuel in fuel cells are attractive ideas that have been investigated for decades. One of the big problems with using hydrogen for this purpose is that hydrogen, due to its small size, can easily escape from its containers, and only low concentrations are required for it to be explosive when mixed with oxygen. To help detect leaks and prevent accidents, a fast and reliable method for the detection of hydrogen gas is necessary. One of the most commonly used materials for this purpose is Pd, due to its ability to absorb H into interstitial sites in its lattice. The problem with Pd is that it is vulnerable to deactivation by several different compounds, one of which being water. This thesis aims to investigate a solution to this by incorporating Pt into the system. Several different compositions were fabricated (Pd70Pt30, Pd85Pt15, Pd90Pt10 and Pd95Pt5), and tested both as a bi-layered structure and alloyed together, in a humidity reactor. All systems show potential as hydrogen sensors in humid environments. However, how to clearly translate the complex signal output into readings of H2 concentration remains unclear.
Keywords: Hydrogen, sensing, nanoparticles, palladium, platinum